Training for Plantation Sector Cooperative Business Empowerment in The Financial Sector in Labuhanbatu Regency in 2021 - Siregar, Muhammad Raja; Limbong, Christine Herawati; Rafika, Mulya; Pitriyani; Elvina; Nasution, Ahmad Yunus (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
This training for empowerment of plantation sector cooperatives in the financial sector aims to increase the knowledge and ability of the cooperative owners or cooperative management in preparing simple financial reports for cooperatives. The government provides financial assistance in the form of a community palm oil rejuvenation program (PSR) with the aim that the community can rejuvenate old or damaged oil palm land into land that can produce high quality palm oil. This is because Labuhanbatu Regency is one of the producers of palm oil and oil palm plantations are also a major factor in supporting the economy of Labuhanbatu Regency. Fund assistance in the form of the community palm oil rejuvenation program (PSR) provided is Rp. 30 million per hectare of oil palm. The funds are given to cooperatives engaged in the plantation sector. The training provided is in the form of training in making simple financial reports for cooperatives. Starting from understanding transaction analysis, accounting terminology, accounting cycles, debit and credit rules, Chart of Accounts (COA), and finally preparing financial statements. Owners or management of cooperatives are very enthusiastic in participating in the training because there are some who just know about the basics of accounting science.